2019
DOI: 10.1177/0361198119839341
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Lane-Based Strategy to Incorporate Mixed Traffic in Interchange Control for Connected and Autonomous Vehicles

Abstract: This work examines the next-generation interchange control system (NIC) that aims to control connected and autonomous vehicles (CAV) at interchanges with the consideration of different mixed traffic cases. The first objective of the paper is to test several parameters including traffic demand, heavy vehicle percentage, communication range, and advance stop line (ASL) to investigate their impact on throughput and delay. The second objective is to incorporate mixed traffic in the NIC, utilizing a lane-based stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Yang et al [20] also found a 50% information level for CVs could significantly decrease the delay and stops by maximizing the speed entering the intersection. However, several studies also found that the intersection performance only improved after certain MPRs of CVs/CAVs are reached [10], [21], [22]. Moreover, several studies found that the models trained with only partial information and the interaction between CAVs and HDVs could result in a negative impact on the intersection system performance [8], [9].…”
Section: B Review Of Studies On Mixed Traffic At the Intersectionmentioning
confidence: 99%
“…Yang et al [20] also found a 50% information level for CVs could significantly decrease the delay and stops by maximizing the speed entering the intersection. However, several studies also found that the intersection performance only improved after certain MPRs of CVs/CAVs are reached [10], [21], [22]. Moreover, several studies found that the models trained with only partial information and the interaction between CAVs and HDVs could result in a negative impact on the intersection system performance [8], [9].…”
Section: B Review Of Studies On Mixed Traffic At the Intersectionmentioning
confidence: 99%
“…However, when a CAV is rejected, it stops at the advance stop line (ASL), which is an early stop line that allows CAV to accelerate and reach a particular speed before reaching the interchange terminal once CAV request is approved later on. The location of ASL is changeable in our NIC model and its effect on the model was tested by Algomaiah and Li [43].…”
Section: A Reservation-based Control For Autonomous Interchangementioning
confidence: 99%